The Pedagogical Competence in Developing Assessment Instruments of Physics High School Teachers in Merauke District - Sari, Desy Kumala; Budiman, Nur Arip; Dinata, Pri Ariadi Cahya; Bahri, Syamsul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to map the ability to develop assessment instruments owned by physics teachers, especially in the Merauke district. The method used in this research is descriptive quantitative. Respondents who were involved in this study were 14 respondents who were physics teachers in Merauke. The data collection instrument used was a questionnaire containing 25 statements. The data of the research results were analyzed using the Ideal Standard Deviation. Overall, physics teachersâ€™ competence in constructing and analyzing items is in the â€œgoodâ€ category, with an average of 90.5. However, some assessment indicators need to be improved, such as reviewing objectives of constructing test instrument, content validation, revising based on validatorâ€™s suggestions, and analyzing the items.